2011
DOI: 10.3324/haematol.2011.042622
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rabbit anti-thymocyte globulin in severe aplastic anemia

Abstract: BackgroundA combination of horse anti-thymocyte globulin and cyclosporine produces responses in 60-70% of patients with severe aplastic anemia. We performed a phase II study of rabbit anti-thymocyte globulin and cyclosporine as first-line therapy for severe aplastic anemia. Design and MethodsTwenty patients with severe aplastic anemia treated with rabbit anti-thymocyte globulin were compared to 67 historical control cases with matched clinical characteristics treated with horse anti-thymocyte globulin. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
62
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 40 publications
(44 reference statements)
14
62
1
2
Order By: Relevance
“…The importance of higher reticulocyte numbers as predictors of response to IST have been noted previously, perhaps reflecting residual HSC numbers. 29,30 Why endogenous pathways do not stimulate normalization of the HSPC compartment, if immune attack has abated, particularly given the very high endogenous circulating levels of TPO in patients with SAA, is unclear. 31,32 It is likely that a critical mass of HSPCs is required for bone marrow recovery in patients, although HSPC numbers remain low even in those who normalize blood counts.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of higher reticulocyte numbers as predictors of response to IST have been noted previously, perhaps reflecting residual HSC numbers. 29,30 Why endogenous pathways do not stimulate normalization of the HSPC compartment, if immune attack has abated, particularly given the very high endogenous circulating levels of TPO in patients with SAA, is unclear. 31,32 It is likely that a critical mass of HSPCs is required for bone marrow recovery in patients, although HSPC numbers remain low even in those who normalize blood counts.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 However, several recent studies on aplastic anemia showed an inferior response and/or decreased survival after rabbit-ATG compared with those after horse-ATG, [16][17][18][19] whereas other studies described comparable results. [20][21][22] Notably, none of the reports indicated a superior efficacy of rabbit-ATG over horse-ATG. The majority of previous reports in adults with MDS have involved horse-ATG, and there are limited data on the efficacy of rabbit-ATG.…”
mentioning
confidence: 99%
“…[17][18][19] No published series of patients with aplastic anemia has shown that rabbit-ATG is superior to horse-ATG in the context of first-line IST. [16][17][18][19][20][21][22] To date, there have only been a few reports on the efficacy of IST with rabbit-ATG in patients with MDS. 10,23,24 In this study, we compared the outcome of IST using horse-ATG with that of IST using rabbit-ATG in a large series of children with RCC.…”
mentioning
confidence: 99%
“…It can produce more profound and prolonged lymphocytopenia 15. In addition, rATG may selectively promote the expansion of regulatory T cells and induce in vivo immune tolerance through this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Manuel G. concluded that despite reports suggesting differences in biological activity of different ATG preparations, rabbit and horse ATG appear to have a similar efficacy for up‐front treatment of severe aplastic anemia 15. Similarly, Shin et al pointed out that the efficacy of both the rATG with CSA and hATG is the same.…”
Section: Discussionmentioning
confidence: 99%